Dexamethasone in anesthesia practice: A narrative review - Teena Bansal; Suresh Singhal; Susheela Taxak; Sukhminder Jit Singh Bajwa (Journal of Anaesthesiology Clinical Pharmacology)
Dexamethasone is routinely used in anesthesia practice and has been regarded as one of the ideal perioperative agents. It is a synthetic glucocorticoid with potent antiinflammatory action. It reduces postoperative nausea and vomiting, pain, postoperative opioid requirements after general anaesthesia as well as spinal anaesthesia. It has been used via intravenous, epidural and perineural routes. It has been used successfully in fascial blocks. It significantly decreases fatigue, shivering and postoperative sore throat and improves quality of recovery.